Inflammasomes and Signaling Pathways: Key Mechanisms in the Pathophysiology of Sepsis - Jhan S. Saavedra-Torres; María Virginia Pinzón-Fernández; Martin Ocampo-Posada; H. A. Nati-Castillo; Laura Alejandra Jiménez Hincapie; Eder J. Cadrazo-Gil; Marlon Arias-Intriago; Marlon Rojas-Cadena; Andrea Tello-De-la-Torre; Walter Osejos; Juan S. Izquierdo-Condoy (Cells, 2025)
Sepsis is a life-threatening syndrome characterized by a dysregulated immune response to infection, frequently leading to multiorgan failure and high mortality. Inflammasomes—cytosolic multiprotein complexes of the innate immune system—serve as critical platforms for sensing pathogen- and damage-associated molecular patterns (PAMPs and DAMPs). Key sensors such as NLRP3, AIM2, and IFI16 initiate caspase-1 activation, IL-1β and IL-18 maturation, and gasdermin D–mediated pyroptosis. In sepsis, excessive inflammasome activation drives oxidative stress, endothelial dysfunction, immunothrombosis, and immune exhaustion. This maladaptive cascade is further aggravated by the release of DAMPs and procoagulant factors, compromising vascular integrity and immune homeostasis. Prolonged activation contributes to immunoparalysis, lymphopenia, and increased susceptibility to secondary infections. Inflammasome signaling also intersects with necroptosis and ferroptosis, amplifying systemic inflammation and tissue injury. Additionally, various pathogens exploit immune evasion strategies to modulate inflammasome responses and enhance virulence. Therapeutic interventions under investigation include selective NLRP3 inhibitors, IL-1 blockers, gasdermin D antagonists, and extracorporeal cytokine hemoadsorption. Emerging approaches emphasize biomarker-guided immunomodulation to achieve personalized therapy. While preclinical studies have shown promising results, clinical translation remains limited. Targeting inflammasomes may offer a path toward precision immunotherapy in sepsis, with potential to reduce organ dysfunction and improve survival.